HAI Snakebite Project In Uganda - Health Action International (HAI) (HEPS-Uganda, 2019)
Conservative global estimates show that snakebite envenoming kills 81,000–138,000 people every year and permanently disables 400,000 more. In Africa, there are an estimated 435,000-580,000 snakebites annually needing treatment, resulting in about 32,000 deaths and 6,000 amputations for sub-Saharan Africa, alone.The economic burden of snakebite is largely under-researched and unknown. However,it is estimated that, for Western Africa, up to USD 6,205 per death could be averted with effective antivenom treatment. The costs of permanent disabilities resulting from snakebite are even higher.The World Health Organization and Member States have started prioritising snakebite envenoming by committing to important policy milestones in recent years. Many survivors of snakebite envenoming are left with a permanent disability, such as a limb amputation and blindness. Survivors are also often plunged further into debt—even destitution—because of high treatment costs and the inability to work.